miRNA Modulation in ALS Spinal Microglia - Matos, Ana Teresa Mateus Aspra de (2022)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease, without cure or specific biomarkers, that involves motor neuron (MN) damage and dysfunctional glial cells. Clinical manifestations include progressive muscle weakness and atrophy, leading to respiratory failure and death within 2 to 5 years from onset. Microglia-driven neuroinflammation was shown to have a central role in MN death and disease progression. Therefore, it is important to identify specific targets that can be modulated to develop effective therapeutic strategies. Lately, miRNAs, which are non-coding RNAs that regulate gene expression, have been indicated as promising diagnostic biomarkers and potential targets for ALS therapies. miRNAs are secreted from cells, change the gene expression of neighbouring ones, and contribute to neuroinflammation propagation. Prior data from our lab identified miRNA(miR)- 124, miR-125b and miR-155, denominated as inflammatory-associated miRNAs, to be upregulated in ALS, namely in microglia isolated from the SOD1G93A mice expressing a human genetic mutation in the superoxide dismutase 1 gene, known as the mSOD1 mouse model. We lately showed that miR-124 drives mSOD1 MN degeneration and glial cell dysfunction, and that anti-miR-124 transfection in MNs recovers the neuro-immune homeostatic signalling. Other studies showed that inhibition of miR-155 and miR-125b in microglia from the spinal cord (neonates) and the cortex (16-week-old females) of mSOD1 mice, respectively, sustain animal survival. However, cellular senescence in ALS remains poorly understood and even less in microglia, the major innate cells of the central nervous system. The goal of the present thesis was to assess the profile of miR-124, miR-125b and miR-155 before and after treatment with their specific inhibitors in the senescent-like microglia, a model opti mized in our laboratory, obtained from the spinal cord of mSOD1 mice with 8-day-old and cultured for 16 days in vitro (16 DIV). We found that the spinal cord 16 DIV mSOD1 microglia have increased levels of miR-124, miR-125b and miR-155 and depressed inflammatory and phagocytic markers. When such microglia were transfected with anti-miR-124, anti-miR-125b and anti-miR-155, we found better protective effects for the first two. When used separately, either anti-miR-124 or anti-miR-125b produce a downregulation of both targeted miRNAs and miR-155 at the same time and were able to increase IL-1β, TNF-α and MFG-E8 gene expression, as well as phagocytic ability, towards wild type non-treated matched micro glia (control) values. Thus, the inhibitors turned the mSOD1 spinal senescent-like mSOD1 microglia into a more polarized phenotype, showing promise to counteract the disease in late stages. When the secretome from such modulated mSOD1 microglia was added to spinal organotypic cultures from mSOD1 mice at early symptomatic stage, IL-10, IL-1β, iNOS and MFG-E8 gene expression levels were enhanced towards control levels. Significant changes for the first two and for MFG-E8 were only ob served with the secretome from spinal 16 DIV mSOD1 microglia transfected with anti-miR-124. In sum, the use of inhibitors for specific hit miRNAs involved in the late stage of disease pro gression due to mSOD1 microglia “dormant” properties may reveal beneficial to recover a neuroprotec tive microglia phenotype in ALS disease.